Hellenia Retz., the correct name for Cheilocostus C.D.Specht (Costaceae) - Govaerts, Rafaël (Phytotaxa, 2013)
In recent years numerous authors have suggested various generic placements for the Crape Ginger but still no valid available name has been published. I therefore give a short overview and make the necessary combinations.